Dyskurs edukacyjny w klasie językowej z perspektywy teorii społeczno-kulturowej - Rokoszewska, Katarzyna (Neofilolog, 2019)
The present paper focuses on classroom discourse from the perspective of Sociocultural Theory. This theory, represented mainly by Vygotsky (1978), Leont'ev (1978) and Wertsch (1985), has been applied to second language acquisition by researchers such as Lantolf (1994). Firstly, the paper presents the view of language and language learning and the main constructs in sociocultural SLA, such as mediation through social interaction, mediation by means of private speech, internalization, the zone of proximal development, and Activity Theory. The methodology of sociocultural research is also taken into consideration. Secondly, the paper describes a number of studies into classroom discourse which are discussed in reference to the constructs mentioned above. Thirdly and finally, the paper provides some evaluation of the theory in question.